HYDROLOGICAL AND HYDROCHEMICAL CHARACTERISTICS OF THE URAL RIVER IN THE WESTERN KAZAKHSTAN REGION - Antipova, N. V. (Science and education №1, 2019)
This article presents the results of a study of the current state of the ecological, hydrological and hydrochemical characteristics of the Ural River, which directly affect the efficiency of natural reproduction of the marketable fish species. The authors present the results of a study of the main hydrological indicators of the reservoir, such as the width, depth and speed of the river during the spring flood and summer low water. The features of the spring flood in 2018 are described in detail with an analysis of the spring rise, peak and decay of flood waters. It is noted that the volume of the annual flow of the Ural River for 2018 is significantly lower than the same indicator for 2017 and amounted to 5,06 km3. The article contains valuable data on the fluctuations in the annual water flow of the Ural River in the territory of West Kazakhstan Oblast over the past 17 years. A detailed hydrography of the Ural River basin within the West Kazakhstan region is given, with the hydrological characteristics of the river network consisting of 7 tributaries and 3 outflows. A hydrochemical analysis of research at five stations of the river on the content of biogenic compounds, the level of mineralization, pH and permanganate oxidation, as well as the gas regime of natural waters is presented.В данной статье представлены результаты изучения современного состояния экологических, гидрологических и гидрохимических характеристик реки Урал, непосредственно влияющих на эффективность естественного воспроизводства промысловых видов рыб. Авторы приводят результаты изучения основных гидрологических показателей водоёма, таких как ширина, глубина и скорость течения реки в период весеннего паводка и летней межени. Подробно описаны особенности весеннего паводка 2018 года с анализом весеннего подъема, пика и спада паводковых вод. Отмечается, что объём годового стока реки Урал за 2018 год значительно ниже аналогичного показателя за 2017 год и составил 5,06 км3. Материалы статьи содержат ценные данные по колебаниям годового водного стока реки Урал на территории Западно-Казахстанской области за последние 17 лет. Приводится развернутая гидрография бассейна реки Урал в пределах Западно-Казахстанской области, с гидрологическими характеристиками речной сети, состоящей из 7 притоков и 3 оттоков. Представлен гидрохимический анализ исследований на пяти станциях реки по содержанию биогенных соединений, уровню минерализации, водородного показателя и перманганатной окисляемости, а также газового режима природных вод.
Keywords: научный журнал; рыбное хозяйство; отечественное издание; промысловые виды рыб; периодическое издание; зко; журнал кксон; паводковые воды; ural river; spawning areas; hydrochemistry; hydrography; hydrology